Incidence and Risk Factors of Heterotopic Ossification in a Matched Cohort Pediatric Population Undergoing Hip Arthroscopy. Issue 5 (31st May 2022) - Feroe, Aliya G.; Flaugh, Rachel A.; Hassan, Mahad M.; Maier, Stephen P.; Cook, Danielle L.; Yen, Yi Meng; Kocher, Mininder S.
Background: The development of heterotopic ossification (HO) is a known complication after hip arthroscopy in adults and has been associated with male sex, older age, larger CAM resection, and obesity. However, the incidence after hip arthroscopy in the pediatric population is not well-documented. Hypothesis/Purpose: The purpose of this retrospective case-control study was to determine the incidence and risk factors for the development of HO in pediatric patients following hip arthroscopy over a ten-year period. Methods: Internal clinical and surgical records from a single pediatric institution were queried to identify all patients under the age of 21 years who underwent hip arthroscopy between 2008 and 2018. For analyses, the 27 cases that developed HO were matched 1:4 on age and sex with 107 controls that did not. Univariate logistic regression analysis was conducted to assess the relationship between demographic and perioperative factors on the development of HO. Multivariate logistic regression was utilized to determine what association, if any, the use of prophylactic NSAIDs (indomethacin 75 mg for three weeks) had on the development of HO when controlling for the change in alpha angle. Results: Twenty-seven of 693 (3.9%) hips that underwent hip arthroscopy developed HO within two years of surgery. The use of indomethacin prophylaxis (n=27) was not significantly associated with the development of HO (n=8, p =0.06), even when controlling for the change in alpha angle ( p =0.12)—nor were age, sex, and BMI percentile (Table 1). For each degree increase in the change in alpha angle, there was an 8% increase in the odds of development of HO (OR=1.08; 95% CI=1.02, 1.15; p =0.01). After controlling for preoperative alpha angle and prophylactic NSAID use, there was a 19% increase in the odds of developing HO for every degree increase in the change in alpha angle (OR=1.19; 95% CI=1.08, 1.31; p <0.001). For each degree increase in the preoperative alpha angle, the odds of developing HO increased by 11% (OR=1.11; 95% CI=1.03, 1.20; p=0.006). Conclusion: The incidence of HO within two years of hip arthroscopy in pediatric patients is 3.9%. Prophylactic indomethacin was not found to be protective against HO, while resection of larger CAM lesions is a risk factor for the development of HO. Although studies in the adult hip arthroscopy population have pointed to a protective role of NSAIDs in HO formation, this relationship may not be applicable to the pediatric population. Table 1. Cohort demographics separated by development of HO (N=134).